Peran UMKM dalam Memacu Pertumbuhan Ekonomi Daerah - Rina Sari (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in regional economic development by generating employment, stimulating local income, and promoting inclusive growth. This study investigates the role of MSMEs in accelerating regional economic growth. Utilizing a mixed‑methods approach, quantitative data from regional economic statistics and qualitative interviews with MSME actors and policy makers were collected in a selected province from 2022 to 2024. The analysis shows that MSMEs contribute significantly to Gross Regional Domestic Product (GRDP), absorb labor especially in non‑formal sectors, and foster local value chains. However, their potential is constrained by limited access to finance, weak managerial capacity, and infrastructure deficits. The findings suggest that well‑targeted policies, capacity building, and institutional support can enhance the effectiveness of MSMEs in driving regional growth. In conclusion, MSMEs are not merely complementary actors but central drivers of regional economic performance, provided that enabling ecosystems are strengthened.